Exercise Training Alters Red Blood Cell Fatty Acid Desaturase Indices and Adipose Tissue Fatty Acid Profile in African Women with Obesity. Issue 8 (6th July 2020) - Nono Nankam, Pamela A.; Mendham, Amy E.; van Jaarsveld, Paul J.; Adams, Kevin; Fortuin‐de Smidt, Melony C.; Clamp, Louise; Blüher, Matthias; Goedecke, Julia H.
Abstract : Objective: This study assessed the changes in red blood cell total phospholipid (RBC‐TPL) and subcutaneous adipose tissue (SAT) fatty acid (FA) composition in response to 12 weeks of exercise training in South African women with obesity and the associations with changes in cardiometabolic risk factors. Methods: Previously sedentary women were randomized into control ( n  = 15) or exercise ( n  = 20) groups. RBC‐TPL and SAT FA profiles, SAT gene expression, systemic inflammatory markers, liver fat, and insulin sensitivity (SI ) were measured before and after the intervention. Results: Compared with control, exercise training induced decreases in RBC‐TPL dihomo‐γ‐linolenic acid content and stearoyl‐CoA desaturase‐1 and increased delta‐5 desaturase–estimated activity ( P  < 0.05). In the combined group, these changes correlated with changes in circulating leptin and TNFα ( P  < 0.05), as well as lower liver fat ( P  < 0.01). Exercise training decreased saturated FA (lauric and myristic acids) and increased polyunsaturated FA (eicosadienoic and adrenic acids) ( P  < 0.05) in abdominal SAT, whereas γ‐linolenic acid decreased ( P  < 0.01) in gluteal SAT. These changes in RBC‐TPL and SAT FA compositions were not associated with changes in SAT gene expression and SI . Conclusions: Exercise training alters RBC‐TPL desaturase activities, which correlate with lower liver fat and systemic inflammation but not with the improvement of SI .